Long-term migratory velocity measurements of single glioma cells using microfluidics. Issue 16 (20th July 2021) - Sengul, Esra; Elitas, Meltem
Abstract : Glioma cells lost their circularity and increased their steady-state velocities; in other words, they adopted an invasive glioma phenotype in the presence of macrophage-depleted medium. Abstract : Microfluidic platforms enabling single-cell measurements notably contribute to the identification and observation of rare cancer cells that are involved in tumor invasion. Most aggressive, invasive, and heterogeneous glioblastoma cells cause incurable primary brain tumors. Infiltrating gliomas of a brain tumor microenvironment have been intensively studied using conventional assays. Still, quantitative, simple, and precise tools are required for long-term, steady-state migratory-velocity measurements of single glioma cells. To measure long-term velocity changes and investigate the heterogeneity of glioma cells under different growth conditions, we developed a microfluidic platform. We cultured U87 glioma cells in the microfluidic device using either regular growth medium or conditional medium composed of 50% basal medium and 50% macrophage-depleted medium. We microscopically monitored the behavior of 40 glioma cells for 5 days. Using acquired images, we calculated cellular circularity and determined the migratory velocities of glioma cells from 60 h to 120 h. The mean migratory velocity values of the glioma cells were 1.513 μm h −1 in the basal medium and 3.246 μm h −1 in the conditional medium. The circularity values of the glioma cells decreased from 0.20–0.25 to 0.15–0.20 when cultured in the conditional medium. Here, we clearly showed that the glioma cells lost their circularity and increased their steady-state velocities; in other words, they adopted an invasive glioma phenotype in the presence of macrophage-depleted medium. Besides, the heterogeneity of the circularity and the velocity of glioma cells were enhanced in the conditional medium.